2012
DOI: 10.1093/hmg/dds302
|View full text |Cite
|
Sign up to set email alerts
|

PACSIN2 polymorphism influences TPMT activity and mercaptopurine-related gastrointestinal toxicity

Abstract: Treatment-related toxicity can be life-threatening and is the primary cause of interruption or discontinuation of chemotherapy for acute lymphoblastic leukemia (ALL), leading to an increased risk of relapse. Mercaptopurine is an essential component of continuation therapy in all ALL treatment protocols worldwide. Genetic polymorphisms in thiopurine S-methyltransferase (TPMT) are known to have a marked effect on mercaptopurine metabolism and toxicity; however, some patients with wild-type TPMT develop toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 42 publications
6
81
2
Order By: Relevance
“…For example, MTHFR C677T and A1298C were reported to be associated with liver dysfunction during maintenance therapy for acute lymphoblastic leukemia in Japanese, 21 and rs2413739 in PACSIN2 was reported to be associated with gastrointestinal toxicity. 22 However, these associations were not as strong as NUDT15 with hair loss and leukopenia, and the results of PACSIN2 were controversial. 23 Pancreatitis is another critical adverse event of thiopurine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MTHFR C677T and A1298C were reported to be associated with liver dysfunction during maintenance therapy for acute lymphoblastic leukemia in Japanese, 21 and rs2413739 in PACSIN2 was reported to be associated with gastrointestinal toxicity. 22 However, these associations were not as strong as NUDT15 with hair loss and leukopenia, and the results of PACSIN2 were controversial. 23 Pancreatitis is another critical adverse event of thiopurine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism is associated with higher concentrations of methylated nucleotide metabolites of 6-MP in cells, as well as higher incidence of severe hepatotoxicity, even after adjustment for TPMT genotype [62][63][64][65][66]. Furthermore, a variant in the PACSIN2 gene has been found to modulate the activity of TPMT and is also independently associated with severe gastrointestinal toxicity due to 6-MP [70]. The UGT1A1*28 polymorphism, which has been associated with Gilbert's syndrome, has also been associated with hyperbilirubinemia during leukemia treatment in one study [30].…”
Section: Gastrointestinal Toxicitymentioning
confidence: 96%
“…A recent study has also provided evidence that TPMT activity may be significantly influenced by PACSIN2 [77], possibly through the latter protein's postulated role in autophagy [78]. RBC TPMT activity was found to be significantly lower in TPMT*1 homozygotes who were heterozygous or homozygous for the minor allele of PACSIN2 SNP rs2413739 (p = 0.031).…”
Section: Do Polymorphisms In Mthfr and Pascin2mentioning
confidence: 96%
“…The PACSIN2 SNP rs2413739 explained 1.8% of the variability in TPMT activity in acute lymphoblastic leukemia patients with a wild-type TPMT genotype, and 31% of the variability in patients who were TPMT*3 heterozygotes [77]. In addition, PACSIN2 SNP rs2413739 was significantly associated with severe gastrointestinal (GI) toxicity in TPMT*1 homozygotes receiving consolidation therapy comprising methotrexate and 6-MP [77] for treatment of acute lymphoblastic leukemia. However, a subsequent study found no evidence of association of PACSIN2 with overall thiopurine-related toxicity in IBD patients (p = 0.378, OR: 0.88, 95% CI: 0.67-1.…”
Section: Do Polymorphisms In Mthfr and Pascin2mentioning
confidence: 99%